Wastewater and Public Health 2015
DOI: 10.1201/b18649-11
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Resistance and Prevalence of Class 1 and 2 Integrons in Escherichia coli Isolated from Two Wastewater Treatment Plants, and Their Receiving Waters (Gulf of Gdansk, Baltic Sea, Poland)

Abstract: Abstract:In order to comprehensively investigate tetracycline resistance in activated sludge of sewage treatment plants, 454 pyrosequencing and Illumina high-throughput sequencing were used to detect potential tetracycline resistant bacteria (TRB) and antibiotic resistance genes (ARGs) in sludge cultured with different concentrations of tetracycline. Pyrosequencing of 16S rRNA gene revealed that tetracycline treatment greatly affected the bacterial community structure of the sludge. Nine genera consisting of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Tetracycline concentrations of ≤1 μg/L selected for both tetA and tetG genes. Selection of tetA and tetG has previously been reported when exposing activated sludge bacteria, diluted in filtrated sewage influent, to very high concentrations of TC (5 and 20 mg/L) for six days (Huang et al, 2014). This indicates some degree of robustness of tetA and tetG as markers for a selection pressure from tetracycline.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Tetracycline concentrations of ≤1 μg/L selected for both tetA and tetG genes. Selection of tetA and tetG has previously been reported when exposing activated sludge bacteria, diluted in filtrated sewage influent, to very high concentrations of TC (5 and 20 mg/L) for six days (Huang et al, 2014). This indicates some degree of robustness of tetA and tetG as markers for a selection pressure from tetracycline.…”
Section: Discussionmentioning
confidence: 72%
“…This indicates some degree of robustness of tetA and tetG as markers for a selection pressure from tetracycline. However, in the study by Huang et al (2014), no effect on either gene was seen at 1 mg/L, the lowest concentration tested. It is unclear if this is a reflection of limited bioavailability of TC, use of an already established community in the assay, and/or fewer bacterial generations studied.…”
Section: Discussionmentioning
confidence: 73%
“…They found that 11 tet genes were present in the sludge, including tetA , tetB , tetC , tetG , tetK , and tetP(A) encoding tetracycline efflux proteins; tetM , tetO , tetS , and tetW encoding ribosomal protection proteins; and tetX encoding enzymatic modification protein. The amount of all of the tet genes increased, while sulII was decreased (Huang et al., ). Similarly, in a bench‐scale activated sludge process with 500 μg/L tetracycline influent, an increase in the proportion of tetA and tetB as well as both tetracycline‐intermediate‐resistant and tetracycline‐resistant heterotrophic bacteria occurred (Yu, Liu, & Li, ).…”
Section: Args In Biological Treatmentmentioning
confidence: 99%
“…In order to observe the ability of activated sludge processes to remove ARGs and ARB, some researchers simulated mechanisms in laboratory‐scale reactors. Huang, Tang, Zhang, Xu, and Ren () sampled activated sludge from a water resource recovery facility in Nanjing, China, and detected the abundance of tetracycline and sulfonamide resistance genes. They found that 11 tet genes were present in the sludge, including tetA , tetB , tetC , tetG , tetK , and tetP(A) encoding tetracycline efflux proteins; tetM , tetO , tetS , and tetW encoding ribosomal protection proteins; and tetX encoding enzymatic modification protein.…”
Section: Args In Biological Treatmentmentioning
confidence: 99%
See 1 more Smart Citation